Recognising laryngeal cancer in primary care: a large case–control study using electronic records - Shephard, Elizabeth A (Br J Gen Pract, 2019)
BACKGROUND: Over 1700 people are diagnosed with laryngeal cancer annually in England. Current National Institute for Health and Care Excellence (NICE) guidelines on referral for suspected laryngeal cancer were based on clinical consensus, in the absence of primary care studies. AIM: To identify and quantify the primary care features of laryngeal cancer. DESIGN AND SETTING: Matched case–control study of patients aged ≥40 years using data from the UK’s Clinical Practice Research Datalink. METHOD: Clinical features of laryngeal cancer with which patients had presented to their GP in the year before diagnosis were identified and their association with cancer was assessed using conditional logistic regression. Positive predictive values (PPVs) for each clinical feature were calculated for the consulting population aged >60 years. RESULTS: In total, 806 patients diagnosed with laryngeal cancer between 2000 and 2009 were studied, together with 3559 age-, sex-, and practice-matched controls. Ten features were significantly associated with laryngeal cancer: hoarseness odds ratio [OR] 904 (95% confidence interval [CI] = 277 to 2945); sore throat, first attendance OR 6.2 (95% CI = 3.7 to 10); sore throat, re-attendance OR 7.7 (95% CI = 2.6 to 23); dysphagia OR 6.5 (95% CI = 2.7 to 16); otalgia OR 5.0 (95% CI = 1.9 to 13); dyspnoea, re-attendance OR 4.7 (95% CI = 1.9 to 12); mouth symptoms OR 4.7 (95% CI = 1.8 to 12); recurrent chest infection OR 4.5 (95% CI = 2.4 to 8.5); insomnia OR 2.7 (95% CI = 1.3 to 5.6); and raised inflammatory markers OR 2.5 (95% CI = 1.5 to 4.1). All P-values were <0.01. Hoarseness had the highest individual PPV of 2.7%. Symptom combinations currently not included in NICE guidance were sore throat plus either dysphagia, dyspnoea, or otalgia, for which PPVs were >5%. CONCLUSION: These results expand current NICE guidance by identifying new symptom combinations that are associated with laryngeal cancer; they may help GPs to select more appropriate patients for referral.